(untitled) (Biological Sciences - PJSIR, 2021)
Maize is an important cereal crop which is directly eaten by humans. The present study was conducted to access the effect of copper chloride on the growth of Zea mays plant. The experiment was carried out in pots. Different concentration of copper chloride (0 ppm as control, 25 ppm, 50 ppm, 75 ppm) were applied to plant before germination and after two weeks of germination. The results showed that there is decreased in growth of Zea mays takes place, while the highest biomass above ground (3.63±0.2 g, 0.29±0.005 g), biomass below ground (2.26±0.15 g, 0.08±0.005 g) total biomass (5.90±0.20 g, 0.29±0.005g) fresh and dry respectively were noted at control. Maximum shoot length (27.86±1.07 cm), root length (2.46±0.15 cm), leaf length (27.93±0.56 cm), leaf width (3.13±0.30 cm), leaf area (65.72±7.68 cm2), number of leaves (9.0±1.0), number of seeds germinate (10.0±0.50) were also noted at control level.